A different visions for uninterruptible load using hybrid solar-grid energy - Mohamed Ibrahim A. Arafa; El-Sayed Soliman A. Said (Institute of Advanced Engineering and Science, 2019)
Attempting to reduce the existing electricity consumption bill, as well as the stability and non-outage grid recharge with the lowest possible cost and suitable quality, is one of the most important goals for those interested in energy around the world. This paper study the circumstances surrounding the Egyptian society to find the best solutions to a achieved this goals, and it was found that solar energy is one of the best alternatives available for energy. Firstly will be study the electricity consumption bill, slice prices and a program was made to calculate the consumption invoice moreover another program for quick estimation to the proposed solar system.The proposed system provides a smart integration between the solar system and grid, where the supply sustainability and the optimal cost are considered. This configuration allows the two sources separately or simultaneously supply the loads depending on photovoltaic extracted energy. Operational analysis of the proposed system will discussed in this paper. The proposed system consists of solar cells, charge controller, batteries and inverter plugged to automatic transfer switches (ATS) using Programmable Logic Control (PLC). The system grantee a safe and reliable load feeding independently on the grid status. The system durability is the most depicted feature through the modelling and experimentally results. A typical case studies for about four years of non-outages photovoltaic-grid hybrid supply (the implemented system) will be presented and discussed.